(3GdfgGjI aj ZQjH GdMOjK hGdCKQs - (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO Hf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s
(3ChdgG (B:s
(3jHOC HMQa GdZjf HGH GdZjf eY GdHGA s
(3BNQgG (B:s
(3ai cJGH GdfHi Ydjg GdSdGe dCbhGd THhg PcQ jHYK , gi HaJM GdjGA GdChdi hVe GdYjf GdegedI (B: (3UbY ef HdGO Gdjef , LYdg dge Je GdLRA GdKGdK hHJeeg fLR SGFQ GdcJGH , hddg GdMeO hGdefg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B272 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B174s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1989s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs